2002
DOI: 10.1177/104225870202600408
|View full text |Cite
|
Sign up to set email alerts
|

Gender, Microenterprise Success and Cultural Context: The Case of South Asia

Abstract: This paper demonstrates weaknesses in the ability of orthodox microenterprise development theory to represent issues relevant to women's success in the sector. Researchers tend to use gender simply as a variable to explain success without understanding gender as a social construct. Such work disregards how culturally specific power relations influence women's opportunities for success. Gender and microenterprise development theorists do better at incorporating power relations into explanations of why women sta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
90
0
5

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(97 citation statements)
references
References 25 publications
2
90
0
5
Order By: Relevance
“…these expectations result in the self-prescribed role of the dutiful daughter and wife and the devoted mother (Jeyaraj 2001, 144). MWEs' acceptance of and commitment to household responsibilities, regardless of them being entrepreneurs, in essence, highlights the male dominance and the influence of the Indian culture and values that make them obedient and submissive to men and conform to the prescribed roles and responsibilities (Jeyaraj 2001;Kantor 2002;pio 2005). As a result, the majority of the women in our sample had a double workload -their business as well as their family -which reduced their energy and commitment and affected their productivity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…these expectations result in the self-prescribed role of the dutiful daughter and wife and the devoted mother (Jeyaraj 2001, 144). MWEs' acceptance of and commitment to household responsibilities, regardless of them being entrepreneurs, in essence, highlights the male dominance and the influence of the Indian culture and values that make them obedient and submissive to men and conform to the prescribed roles and responsibilities (Jeyaraj 2001;Kantor 2002;pio 2005). As a result, the majority of the women in our sample had a double workload -their business as well as their family -which reduced their energy and commitment and affected their productivity.…”
Section: Discussionmentioning
confidence: 99%
“…Research has identified multiple factors -human capital, culture, family, institutional factors, gender and social capital -as possible barriers for MWEs (Azmat 2013). MWEs also encounter gender-neutral challenges such as access to capital and restrictive government regulations and a lack of local knowledge, culture and language (Raijman and Semyonov 1997;Kantor 2002;volery 2007;Dhaliwal, Scott, and Hussain 2010).…”
Section: Ethnicity Gender and Women's Entrepreneurshipmentioning
confidence: 99%
“…Some researchers (such as Bandura, 1997) believe that self-efficacy is the most important element in empowerment, since it determines whether people will try and persist in attempting to accomplish a difficult task. Kantor (2002) argues that empowerment and innovative behaviour are inextricably linked.…”
Section: Background To the Studymentioning
confidence: 99%
“…A més, recentment, les investigacions tendeixen a donar rellevància a la variable gènere per explicar la creació i l'èxit de les empreses (Kantor, 2002). A partir d'aquest fet, ha sorgit una literatura entorn del denominat «despertar femení» i/o «emprendre femení», aplicat a la creació i gestió d'empreses.…”
Section: Marc Teòric I Estratègia De La Investigacióunclassified